Super-8 in Calcutta. Analysis of a "Failed" Movement - Biswas, Amrita (Iluminace, 2022)
The Super-8 films that flourished in the city of Calcutta during the 1980s had been central to a very conscious film movement that wanted to propagate the culture of non-commercial filmmaking by organizing film festivals and workshops on the format. The movement played a pivotal role in Calcutta's film culture because it initiated film enthusiasts to a new horizon of filmmaking where anybody, on a shoestring budget, could narrate a story or document an event that the mainstream media would not cover.However, the discourse around the movement was one of failure that witnessed the production of poor-quality films. There has also been a conspicuous critical as well as archival lacuna in chronicling Calcutta's Super-8 movement. Thus, to learn about the movement, I had to meet film society activists of the era and listen to anecdotes until I was integrated into cultural networks that helped me access the archives of personal collectors. An examination of the personal archives renders prominence to the transnational collaboration that the movement had witnessed, besides the horizon of expectations that the format had stimulated in the realms of film production and circulation. This paper shifts the emphasis on Super-8 from the "quality" of the films produced and the associated notion of "failure" of the movement to the filmic possibilities that the technological format had enabled. It thereby analyses the movement's critical role in stimulating aspiration towards a participatory practice of alternative filmmaking in Calcutta. It reads such practices as a form of politico-cultural activism.
Keywords: activism; alternative; network; film movement; Calcutta